Attitudes About Forgiveness and Leaving a Relationship: The Context of Relationship Aggression - Ermer, Ashley E. (Journal of interpersonal violence, 2022)
The present study examines participant attitudes regarding whether a victim of IPV should forgive an offending partner and whether they should stay or leave a violent relationship. A total of 562 participants completed the study, which entailed responding to factorial vignettes online. Participants were primarily heterosexual, female, non-Latino, and White, with an average age of 21.75. Using logistic regressions, participants were significantly more likely to think the victim should forgive the perpetrator if the perpetrator was female and for less severe acts of aggression. Multinomial logistic regressions found that respondents were significantly less likely to state ?yes? or ?it depends,? compared to ?no,? as to whether the victim should leave the relationship when the aggression was more severe and were more likely to say a male victim should stay in a violent relationship than a female victim. Qualitative analyses found three main themes regarding whether a victim should forgive: (1) context matters; (2) forgiveness is best ? with caveats; and (3) questioning how often violence had occurred. With regard to whether a victim should leave an aggressive relationship, two main themes emerged: (1) situation matters ? especially the relationship context and (2) questioning whether the violence had occurred before. This study provides insight into attitudes, by those external to a couple, regarding forgiveness and leaving a relationship after an instance of relationship aggression and has implications for both practitioners and policymakers. The constructed views about leaving a relationship may spill over into decisions regarding whether to implement policy surrounding IPV. Practitioners should also be cognizant of the varying definitions of forgiveness when working with clients who have experienced IPV as a practitioner?s definition of forgiveness may not necessarily align with a client?s definition.